Alexander Lamb Cullen OBE. 30 April 1920—27 December 2013. (30th April 2018) - Davies, J. Brian
Abstract : Alex Cullen combined the sharpest of scientific minds with a gentle personality and a great sense of humour. He was Professor and Head of the Department of Electrical Engineering at Sheffield from 1955 to 1967, and then Head of the Department of Electrical Engineering at University College London (UCL) until 1980. He continued his research there as a Science and Engineering Research Council Senior Fellow until 1985, and for some years as Research Fellow of UCL. His research concerned electromagnetic waves over a wide range of microwave devices and measurement techniques, the latter at a fundamental level. These contributions were of a highly innovative and 'ground-breaking' nature. He was appointed OBE in 1960, and elected Fellow of the Royal Society in 1977. He was an accomplished jazz musician, playing drums and clarinet. He was a signatory of a letter to The Times in January 1986, calling on Prime Minister Margaret Thatcher to 'Save British Science'. This led to the foundation of the Save British Science pressure group, now the Campaign for Science and Engineering (CaSE), which has built up an enviable reputation with politicians and the media in representing the concerns of scientists and engineers. When (now Sir) Eric Ash left UCL in 1985 to become Rector of Imperial College, he remarked that Alex was 'the last gentleman in the business'.